(untitled) (Relegere: Studies in Religion and Reception, 2017)
Hugo Chávez (1954–2013), the former president of Venezuela (1999–2013), brought Latin American populism to a global audience through his rhetorical remarks and controversial appearance in the global media. Theological and biblical metaphors were part of this rhetoric. The article argues that Chávez’s appropriation of theological metaphors in his populist political discourse could be considered as a symptom of the continuing influence and relevance of liberation theology in Latin America during the two last decades of victorious leftism on the continent. On one hand, liberation theology as a social movement had been weakened, especially within the Catholic Church. On the other, the bureaucratic language from the neoliberal era, tied to the Washington consensus, was to a high degree exhausted and replaced by a populist language that paved the way for the inflow of religious and Christian metaphors into politics. Chávez’s use of these metaphors in a way that was consistent with liberation theology points to Christian and Latin American liberationist discourse as a crucial factor in the resurgence of the political left within a religiously vibrant region